Injury profile of an Iranian professional soccer team, in the Premier League - Hassabi, M.; Mortazavi, S. M. -J.; Giti, M. R.; Hassabi, M.; Mansournia, M. -A.; Shapouran, S. (Asian Journal of Sports Medicine, 2010)
Purpose: Despite numerous studies which have been done regarding soccer injuries worldwide, there is lack of available data considering the epidemiology of injuries in the Iranian soccer premier league, although it is the most popular sport in the country. The main goal of this research was to determine the incidence of physical injuries in the studied population, considering other characteristics such as site, type and mechanism as well. Methods: Twenty one adult male professional soccer players (age 24±3), members of a team (Tehran-Pas) participating in Iranian premier league, were followed during a 4-month period. The injury characteristics and exposure times were recorded by the team physician during all the matches and training sessions. Results: The total exposure time was 2610 playing hours (2352 h of training versus 258 h of competition). Eighty six percent of the injuries were acute. Incidence of acute injuries was 16.5 (95% CI: 12-22) per 1000 hours of playing (11.5 per 1000 hrs of training and 62 per 1000 hrs of competition). The most common types of injuries were strains followed by contusions, each of which constituted 30% of acute injuries. More than 80% of injuries occurred in lower limbs, especially in thigh and groin regions. Nearly 60% of acute injuries occurred in dominant side of the body, and collision was the reason of about half of the acute injuries. Severity of more than 70% of the injuries was minor. On average each injury had led the player being off the field for about 10 days. Conclusion: The incidence of injury in this research is in range of numbers obtained in important international tournaments but the rate of injuries during training sessions is higher than comparable studies.